2017
DOI: 10.3892/etm.2017.5535
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside protects myocardial cells from apoptosis through suppression of the TLR4/NF-κB signaling pathway

Abstract: Astragaloside is a monomer isolated from Astragalus membranaceus, a flowering plant in the family Fabaceae. The aim of the present study was to investigate the anti-apoptotic affect of astragaloside on myocardial cells through the TLR4/NF-κB signaling pathway. Astragaloside, NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC) and Toll-like receptor 4 (TLR4) blocking antibody solution were prepared in vitro, and myocardial cells were incubated and cultured in serum-free medium overnight. Cells were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that β-D-mannuronic acid inhibited the activity of AS by blocking the TLR2/4/NF-κB pathway (55,56). Zhao et al (58) reported that astragaloside protected myocardial cells against cell apoptosis by suppressing the TLR4/NF-κB pathway. Therefore, the expression of NF-κB pathway in patients with AS, and PBMCs from these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that β-D-mannuronic acid inhibited the activity of AS by blocking the TLR2/4/NF-κB pathway (55,56). Zhao et al (58) reported that astragaloside protected myocardial cells against cell apoptosis by suppressing the TLR4/NF-κB pathway. Therefore, the expression of NF-κB pathway in patients with AS, and PBMCs from these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Calycosin can effectively inhibit allergic inflammation and has anti-inflammatory properties ( 32 ). Astragaloside has been found to prevent myocardial cell apoptosis and protect myocardial cells, which is a kind of potential drug in the prevention of heart failure ( 33 ). Astragaloside IV has been found to have both antioxidant and anti-inflammatory activities ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…18) Astragaloside, another active substance of astragalus, showed anti-apoptotic effects in myocardial cells and reduced acute myocardial infarction, which was associated with inactivation of the toll-like receptor 4 (TLR4)/nuclear factor (NF)-κB signaling pathway. 19,20) Astragalus polysaccharide could also ameliorate myocardial inflammation and fibrosis by blocking the TLR4/NF-κB pathway in mice with coxsackievirus B3induced viral myocarditis. 21) These findings provide a basis for in-depth analysis of the function of astragalus extracts in HF.…”
Section: Discussionmentioning
confidence: 99%